Comparative evaluation of gingival response following the placement of light-cured dressing and noneugenol dressing after periodontal flap surgery: A clinical study - Saransh Srivastava; Priyanka Tandon; Himani Sharma; Stuti Gupta (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study was to compare light-cured dressing with most widely used noneugenol pack in the perspective of esthetics, acceptance, and healing following periodontal flap surgery. Materials and Methods: Fifty-eight patients suffering from generalized chronic periodontitis, requiring periodontal flap surgery on contralateral sides of the arch, were selected and divided randomly into Group I (control) and Group II (test). In Group I, a noneugenol dressing and in Group II light-cured dressing were applied after flap surgery. Clinical parameters such as debris index, plaque index, and modified gingival index were recorded at baseline (day 0) and 10 days postoperatively (after removal of the dressing). The data were collected and statistically analyzed. Results: Group II showed better results than Group I when debris index, plaque index, and modified gingival index scores were compared though the differences were not statistically significant. Patients found no unpleasant taste/smell and perceived the light-cured dressing to be better. Conclusion: The noneugenol dressing retained more plaque on its undersurface than light-cure dressing. However, this did not have much influence on the healing outcome and clinical gingival parameters, which were optimal and comparable in both groups. The greater number of patients showed a preference for light-cure dressing, based on its superior esthetics and taste.